Experimental and Computational Crushing Behaviour of Laminated Composite Shells - Saad, Elsadig Mahdi Ahmed (2000)
This thesis presents the effect of structural geometry, reinforcement type and hybridisation on the crushing behaviour, energy absorption, failure mechanism and failure mode of cylindrical, conical and compound composite shell. The static crushing behaviour of cylindrical, conical and compound composite shell under uniform axial load has been investigated, experimentally, analytically and numerically. Four types of composites were tested, namely, carbon fibre/epoxy, glass fibre/epoxy, oil palm frond fibre/epoxy and the carbon-glass hybrid. This work also examines the effect of the residual stresses built on the crushing behaviour; energy absorption, failure mechanism and mode of failure of the filament wound laminated circular conical composite shell. For the circular cylindrical and conical shells, the cones vertex angles tested were 0, 6, 12,and ISO. Results for the glass/epoxy circular cylindrical shell show that the stress distribution is constant along the shell generator. On the other hand results for the glass/epoxy circular conical shells with vertex angles of 6, 12 and 18 degrees show that the stress distribution is sensitive along the shell generator. As the vertex angle increases, the average crushing load increases, while the initial failure load decreases. The compound shells used in this investigation were the cone-cone and conecylinder- cone intersection composite shells. For the cone-cone intersection shells, the cone vertex angles were 10°, 15°, 20° and 25°. While for the cone-cylinder-cone, the cone vertex angles are 10° and 15° and the cylindrical part lengths were varied between 0 and 50mm. The results showed that the initial failure was dominated by interfacial and shear failure, while the delamination and eventually fibre fracture dominated the failure mechanism after the initial first failure. For the circular cylindrical and conical shells, the proposed analytical solution well predicts the initial failure load for the circular cylindrical and conical laminated composite shells. The failure criteria used to predict the initial failure show an excellent agreement. For the cone-cone intersection composite shell, the results showed that the structures with vertex angles 20° and 25° exhibited good energy absorption capability. For the cone-cylinder-cone, numerical results show that high-localised stress has been concentrated at the junctions between the cylinder and cones. Experimental results showed that structures of cylindrical part length varies between 10 and 20mm exhibited good energy absorption capability and stands a very high crushing load.